Chymase inhibitor ameliorates hepatic steatosis and fibrosis on established non‐alcoholic steatohepatitis in hamsters fed a methionine‐ and choline‐deficient diet. Issue 9 (10th January 2013) - Masubuchi, Shinsuke; Takai, Shinji; Jin, Denan; Tashiro, Keitaro; Komeda, Koji; Li, Zhong‐Lian; Otsuki, Yoshinori; Okamura, Haruki; Hayashi, Michihiro; Uchiyama, Kazuhisa
Abstract : Aim: Chymase plays a role in the augmentation of angiotensin II formation, which is involved in liver fibrosis. The therapeutic effects of a chymase inhibitor, TY‐51469, on established hepatic steatosis and fibrosis were investigated in a model of developed non‐alcoholic steatohepatitis. Methods: Hamsters were fed a normal diet or methionine‐ and choline‐deficient (MCD) diet for 12 weeks. Then, treatment with TY‐51469 (1 mg/kg per day) or placebo was initiated, and the treatment was continued concurrently with the MCD diet for an additional 12 weeks. Results: At 12 weeks after initiating the MCD diet, marked hepatic steatosis and fibrosis were observed in MCD diet‐fed hamsters. Malondialdehyde and gene expression levels of collagen I, collagen III, α‐smooth muscle actin (α‐SMA) and Rac‐1 in liver extracts were also increased in the MCD‐diet‐fed hamsters at 12 weeks. At 24 weeks, hepatic steatosis and fibrosis were more prominent in the placebo‐treated hamsters that were fed the MCD‐diet for 24 weeks versus 12 weeks. Hamsters treated with TY‐51469 for 12 weeks after being on a 12‐week MCD diet had significant ameliorations in both hepatic steatosis and fibrosis, and there were no significant differences compared to normal diet‐fed hamsters. There were significant augmentations in angiotensin II and malondialdehyde, and gene expressions of collagen I, collagen III, α‐SMA and Rac‐1 in the placebo‐treated hamsters at 24 weeks; however, these levels were reduced to normal levels in the TY‐51469‐treated hamsters. Conclusion: TY‐51469 not only prevented the progression of hepatic steatosis and fibrosis, but also ameliorated hepatic steatosis and fibrosis.